Competência gerencial do bibliotecário em contextos empresariais : um estudo fenomenográfico - Batista, Carla Erler Mattos (2018)
The main objective of this research is to analyze the different conceptions of management that influence the development of management skills of librarians who act as managers in the informational area in companies from the state of Espírito Santo. For th